Intravenous brivaracetam in status epilepticus: A multicentric retrospective study in Italy. (March 2021) - Orlandi, Niccolò; Bartolini, Emanuele; Audenino, Daniela; Coletti Moja, Mario; Urso, Lidia; d'Orsi, Giuseppe; Pauletto, Giada; Nilo, Annacarmen; Zinno, Lucia; Cappellani, Roberto; Zummo, Leila; Giordano, Antonello; et al.
Highlights: BRV proved to be useful and safe for the treatment of status epilepticus. Time to seizures resolution appears shorter when it is administered in the early phases of status epilepticus. The use of the BRV within 6 h from SE onset was independently associated to an early seizures' resolution. No severe treatment emergent adverse events were observed. Abstract: Purpose: to evaluate the use, effectiveness, and adverse events of intravenous brivaracetam (BRV) in status epilepticus (SE). Methods: a retrospective multicentric study involving 24 Italian neurology units was performed from March 2018 to June 2020. A shared case report form was used across participating centres to limit biases of retrospective data collection. Diagnosis and classification of SE followed the 2015 ILAE proposal. We considered a trial with BRV a success when it was the last administered drug prior the clinical and/or EEG resolution of seizures, and the SE did not recur during hospital observation. In addition, we considered cases with early response, defined as SE resolved within 6 h after BRV administration. Results: 56 patients were included (mean age 62 years; 57 % male). A previous diagnosis of epilepsy was present in 21 (38 %). Regarding SE etiology classification 46 % were acute symptomatic, 18 % remote and 16 % progressive symptomatic. SE episodes with prominent motor features were the majority (80 %). BRV was administered as first drug after benzodiazepine failure in 21 % episodes, while it was used as the second or the third (or more) drug in the 38 % and 38 % of episodes respectively. The median loading dose was 100 mg (range 50−300 mg). BRV was effective in 32 cases (57 %). An early response was documented in 22 patients (39 % of the whole sample). The use of the BRV within 6 h from SE onset was independently associated to an early SE resolution (OR 32; 95 % CI 3.39–202; p = 0.002). No severe treatment emergent adverse events were observed. Conclusion: BRV proved to be useful and safe for the treatment of SE. Time to seizures resolution appears shorter when it is administered in the early phases of SE.